2013
DOI: 10.1016/j.pmcj.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The mobile fitness coach: Towards individualized skill assessment using personalized mobile devices

Abstract: a b s t r a c tWe report on our extended research on GymSkill, a smartphone system for comprehensive physical exercising support, from sensor data logging, activity recognition to on-top skill assessment, using the phone's built-in sensors. In two iterations, we used principal component breakdown analysis (PCBA) and criteria-based scores for individualized and personalized automated feedback on the phone, with the goal to track training quality and success and give feedback to the user, as well as to engage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(110 citation statements)
references
References 24 publications
2
105
0
3
Order By: Relevance
“…Some studies have examined the use of wearable medical technology for chronic health conditions such as diabetes with promising results (Georga, Protopappas, Bellos, & Fotiadis, 2014). Most commercially available health trackers are geared toward fitness and exercise, obviously with promising effects on physical activity (Kranz et al, 2013 …”
Section: Mobile and Wearable Technology For Healthmentioning
confidence: 99%
“…Some studies have examined the use of wearable medical technology for chronic health conditions such as diabetes with promising results (Georga, Protopappas, Bellos, & Fotiadis, 2014). Most commercially available health trackers are geared toward fitness and exercise, obviously with promising effects on physical activity (Kranz et al, 2013 …”
Section: Mobile and Wearable Technology For Healthmentioning
confidence: 99%
“…As reviewed elsewhere (Lomborg and Frandsen 2015;Lupton 2016), existing research developed at the intersection of computer science and health studies treats personal self-tracking data as already having predetermined meaning and value, which can be mobilised in order to change the user's behaviour. The concerns in this field of research, therefore, have two key foci when it comes to user-oriented studies: the deployment of self-tracking for improving health through lifestyle interventions (see for example Turner-McGrievy et al 2013;Wang et al 2014); and how self-tracking technologies might be designed to motivate behaviour change on the basis of particular user experiences (see for example Kranza et al 2013)). …”
Section: Personal Data Epistemologiesmentioning
confidence: 99%
“…Nor does the scholarship in fitness apps more broadly include much work on the qualitative dimensions of their use. Existing research on mobile fitness apps is dominated by quantitative work within a positivist framework of behavior change (Conroy, Yang, & Maher, 2014;West et al, 2012;Kranz et al, 2012;Chen & Pu, 2014;Millington, 2014;Lister, West, Cannon, Sax, & Brodegard, 2014). Conroy et al (2014) found that the top ranked fitness mobile apps can be categorized as either educational or motivational, and the most common behavior change techniques used in those apps include providing information or demonstrating specific physical activities.…”
Section: Gaps In the Literaturementioning
confidence: 99%